Pengaruh Kualitas Informasi , Kualitas Layanan , Dan Kemudahan Transaksi Terhadap Kepuasan Pelanggan Dengan Variabel Intervening Keamanan - Kurniawati, Veni; Azizah, Nurul (Program Pascasarjana STIE Amkop Makassar, 2023)
KAI Acess is an online train ticket purchase application with an online payment method. The update of the KAI Access application is also a form of innovation and solution in presenting orders for various KAI Group services in one hand. The type of research used in this research is to use quantitative methods with surveys obtained through a list of questions or questionnaires of respondents. The technique used in this research is the PLS-SEM 4.0 model. The instruments used include information quality, service quality, transaction convenience, user security, and customer satisfaction using KAI Acess. The conclusion from this study is that the quality of information on KAI Access can be considered good. Because KAI Access has been able to provide relevant information to its users. , the quality of service at KAI Access is also very good. KAI Access is able to provide services to KAI Access customers such as selecting seats according to passenger requests, the convenience of transactions provided by KAI Access is able to help customers who do not have cash in making payments online, besides that there is an influence on user security on customer satisfaction. Keywords: Quality of Information, Quality of Service, Ease of Transactions, Customer Satisfaction